2008
DOI: 10.1021/ic701680c
|View full text |Cite
|
Sign up to set email alerts
|

Multifrequency Pulsed Electron Paramagnetic Resonance Study of the S2 State of the Photosystem II Manganese Cluster

Abstract: Multifrequency electron spin-echo envelope modulation (ESEEM) spectroscopy is employed to measure the strength of the hyperfine coupling of magnetic nuclei to the paramagnetic (S = 1/2) S2 form of photosystem II (PSII). Previous X-band-frequency ESEEM studies indicated that one or more histidine nitrogens are electronically coupled to the tetranuclear manganese cluster in the S2 state of PSII. However, the spectral resolution was relatively poor at the approximately 9 GHz excitation frequency, precluding any i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
61
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(80 citation statements)
references
References 105 publications
(227 reference statements)
18
61
0
1
Order By: Relevance
“…The spin density distribution on the manganese cluster has also been obtained by QM/MM (quantum mechanics/molecular mechanics) calculations (40,41). These studies showed that the largest spin density is ϳ2 and distributed on Mn1, and the spin densities for other manganese are ϳ1, which are in agreement with those obtained from the ESEEM measurements (28). On the other hand, the sign of the spin densities was inconsistent between the pulsed ELDOR results (30) and theoretical studies, because the former showed a spin topology of ␣␤␣␤, whereas the latter showed a ␣␤␤␣ topology.…”
Section: ؉supporting
confidence: 75%
See 1 more Smart Citation
“…The spin density distribution on the manganese cluster has also been obtained by QM/MM (quantum mechanics/molecular mechanics) calculations (40,41). These studies showed that the largest spin density is ϳ2 and distributed on Mn1, and the spin densities for other manganese are ϳ1, which are in agreement with those obtained from the ESEEM measurements (28). On the other hand, the sign of the spin densities was inconsistent between the pulsed ELDOR results (30) and theoretical studies, because the former showed a spin topology of ␣␤␣␤, whereas the latter showed a ␣␤␤␣ topology.…”
Section: ؉supporting
confidence: 75%
“…EPR spectroscopy has been used to characterize the manganese cluster (23)(24)(25)(26) extensively, and a typical, S 2 state multiline signal centered at g ϭ 2 has been well characterized. The multiline signal showed 19 -21 peaks in a range over ϳ180 mT width, and its properties have been studied by several advanced EPR techniques such as 55 Mn-ENDOR (27), ESEEM (28,29), and pulsed ELDOR (30). The ENDOR results indicated that the S 2 state is composed of one Mn(III) and three Mn(IV), where the Mn(III) ion is assigned to the Mn1 ion in the crystal structure ( Fig.…”
Section: ؉mentioning
confidence: 99%
“…In the recent x-ray crystallographic structural models of PSII, the Mn 4 Ca cluster is ligated by a single histidine residue, His 332 of the D1 polypeptide (8 -11). This assignment is supported by recent 31-34 GHz ESEEM studies of the Mn 4 Ca cluster in its S 2 state (15,16). These studies show that the nitrogen couplings observed in earlier ESEEM studies conducted at lower frequencies (9 -12 GHz) (17)(18)(19)(20) originate from a single 14 N nucleus.…”
supporting
confidence: 66%
“…These studies show that the nitrogen couplings observed in earlier ESEEM studies conducted at lower frequencies (9 -12 GHz) (17)(18)(19)(20) originate from a single 14 N nucleus. The higher frequency studies permit the quantitative determination of the hyperfine and nuclear quadrupolar couplings of the coupled nucleus; the higher frequency studies are consistent with direct coordination of the 14 N atom to a manganese ion in the S 2 state (15,16). On the basis of earlier 9-GHz ESEEM studies conducted with unlabeled and […”
mentioning
confidence: 59%
“…Extensive X-ray diffraction (XRD) studies using synchrotron radiation (SR) (16)(17)(18)(19)(20)(21) and various spectroscopic techniques (22)(23)(24)(25)(26)(27)(28)(29) have been used over the last several decades to elucidate the structure and mechanism of the OEC in PS II. Among the various methods, XRD is clearly the technique of choice for obtaining an overall detailed structure of PS II and the Mn 4 CaO 5 cluster.…”
mentioning
confidence: 99%